2011
DOI: 10.1021/ja2043276
|View full text |Cite
|
Sign up to set email alerts
|

NIR-Light-Induced Deformation of Cross-Linked Liquid-Crystal Polymers Using Upconversion Nanophosphors

Abstract: When upconversion nanophosphors were incorporated into an azotolane-containing cross-linked liquid-crystal polymer film, the resulting composite film generated fast bending upon exposure to continuous-wave near-IR light at 980 nm. This occurs because the upconversion luminescence of the nanophosphors leads to trans-cis photoisomerization of the azotolane units and an alignment change of the mesogens. The bent film completely reverted to the initial flat state after the light source was removed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
185
0
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 290 publications
(188 citation statements)
references
References 55 publications
2
185
0
1
Order By: Relevance
“…10a). 88 Here, the upconversion luminescence (UCL) of the nanophosphors not only induces trans-cis photoisomerization of the azo groups but also leads to alignment change of the mesogens. Under excitation with a CW 980 nm laser, the as-prepared UCNPs shows blue emission and the main UCL emission peaks at 450 nm and 475 nm overlap the absorption band of the azotolane CLCP film (between 320 nm and 550 nm) perfectly as shown in Fig.…”
Section: Deformation Of Crosslinked Liquid-crystalline Polymers Inducmentioning
confidence: 99%
“…10a). 88 Here, the upconversion luminescence (UCL) of the nanophosphors not only induces trans-cis photoisomerization of the azo groups but also leads to alignment change of the mesogens. Under excitation with a CW 980 nm laser, the as-prepared UCNPs shows blue emission and the main UCL emission peaks at 450 nm and 475 nm overlap the absorption band of the azotolane CLCP film (between 320 nm and 550 nm) perfectly as shown in Fig.…”
Section: Deformation Of Crosslinked Liquid-crystalline Polymers Inducmentioning
confidence: 99%
“…Thermomechanical actuation of soft materials is generally based on a reversible thermodynamic volume change due to phase transition or thermoisomerization in the bulk solid state, [38][39][40][41][42][43] whereas the optical change of CPs is primarily caused by variations in the electronic structure. Therefore, if the PDPA matrix is infiltrated with a certain PCM, and the polymer matrix undergoes further changes in the volume and electronic structure simultaneously during the phase change of the PCM, the PCM-incorporated PDPA film can act as a unique multifunctional hybrid material that exhibits both optical and thermomechanical responses to latent heat.…”
Section: Introductionmentioning
confidence: 99%
“…Structural Analysis of NaYF 4 : 20 mol%Yb 3+ , 1 mol%Tm 3+ UCNPs According to our reported work, the UCNPs showed uniform nanocrystals with an average diameter of ∼70 nm from TEM image [17]. The XRD analysis of as-prepared UCNPs was performed.…”
Section: Resultsmentioning
confidence: 95%
“…Most recently, we reported that with combination of a monodomain azotolanecontaining CLCP film and NaYF 4 :Yb,Tm upconversion nanophosphors (UCNPs), the resulting CLCP/UCNP composite film generated fast bending along the alignment direction upon irradiation with continuous-wave (CW) NIR light at 980 nm [17]. In this paper, to further verify that the bending deformation of the CLCP/UCNP composite film is induced by the photochemical process, not only the monodomain composite film but also a polydomain composite film were prepared to investigate the mechanism of NIR-light-induced deformation.…”
Section: Introductionmentioning
confidence: 99%